IMPLEMENTATION OF VE.RUBRIC BASED ON HOTEL SOP ON HOUSEKEEPING COMPETENCY TEST IN HOUSEKEEPING VOCATIONAL HIGH SCHOOL - Neni Rohaeni; Nenden Rani Rinekasari; Yoyoh Jubaedah; Shofa Fithriturrohmi Yusuf (Journal of Architectural Research and Education, 2022)
This research is motivated by the need for a performance assessment on the Housekeeping competency test at Hospitality Accommodation vocational high school which can measure the competence of students objectively according to the Hotel SOP. This research is the implementation stage of Ve.Rubric based on Hotel SOP on the Housekeeping competency test which has been tested for validation through expert judgement at Hospitality Accommodation vocational high school. The method used in this study is a descriptive method, by choosing the location of the Hospitality Accommodation Vocational School in West Java. The purpose of this study is to implement Ve.Rubric based on Hotel SOP in the Housekeeping competency test at Hospitality Accommodation vocational high school to determine the feasibility of the application developed from user responses. Research participants were selected by students and teachers who teach Housekeeping subjects at Accommodation Hospitality vocational high school as well as hotel practitioners in West Java. The findings showed that Ve.Rubric based on Sop Hotel was declared very feasible and the interrater reliability result data obtained by the cronbach alpha value of 0.818 had good reliability on very high criteria. Usability analysis obtained the results that, Ve.Rubric provides convenience in assessing performance at the time of competency tests and is more effective and feels satisfied as a user. The results of this study contain the implication that, Ve.Rubric based on Hotel SOP can be implemented on the Housekeeping competency test at SMK Hospitality Accommodation both in West Java and in other provinces in the wider clause.